From Whence Cometh My Help? Psychological Distress and Help-Seeking in the Evangelical Christian Church - Lloyd, Christopher E. M.; Reid, Graham; Kotera, Yasuhiro (Frontiers in Psychology, 2021)
Seeking professional help for psychological distress is generally associated with improved outcomes and lower levels of distress. Given the saliency of religious teachings, it has been shown that aspects of Christian belief may influence adherents’ attitudes towards mental health help-seeking. Based on existing research on American Evangelicals, it was hypothesised that religious social support would positively predict attitudes towards mental health help-seeking, whilst fundamentalism, mental distress, and the belief that psychopathology is caused by immoral or sinful living would negatively predict participants’ attitudes. On a convenience sample of 252 British Evangelicals, our hypotheses were supported and these variables significantly predicted participants’ attitudes towards seeking mental health help, F(7,243) = 9.64, p < .001, R2 = .195. These findings together suggest that whilst religious support positively predicts help-seeking attitudes, Evangelical fundamentalism, in addition to beliefs that mental illness has a spiritual cause, as well as experiences of mental distress may be associated with more negative attitudes towards psychotherapeutic intervention. Thus, mental health practitioners should be aware of clients’ religious worldviews and tailor interventions appropriately, acknowledging that working with religious organisations may yield the most positive outcomes for patients.